3D displacement field retrieved by integrating Sentinel-1 InSAR and GPS data: the 2014 South Napa earthquake. Issue 1 (1st January 2016) - Polcari, Marco; Palano, Mimmo; Fernández, José; Samsonov, Sergey V.; Stramondo, Salvatore; Zerbini, Susanna
Abstract: In this study the integration of Sentinel-1 InSAR (Interferometric Synthetic Aperture Radar) and GPS (Global Positioning System) data was performed to estimate the three components of the ground deformation field due to the Mw 6.0 earthquake occurred on August 24th, 2014, in the Napa Valley, California, USA. The SAR data were acquired by the Sentinel-1 satellite on August 7 th and 31 st respectively. In addition, the GPS observations acquired during the whole month of August were analyzed. These data were obtained from the Bay Area Regional Deformation Network, the UNAVCO and the Crustal Dynamics Data Information System online archives. The data integration was realized by using a Bayesian statistical approach searching for the optimal estimation of the three deformation components. The experimental results show large displacements caused by the earthquake characterized by a predominantly NW-SE strike-slip fault mechanism.